Bird community structure and host plant in Sukamade Resort, Meru Betiri National Park, East Java, Indonesia - ABDU ROHMAN; DICKY WAHYUDI; WACHJU SUBCHAN; JUMADIAWAN JUMADIAWAN (Society for Indonesian Biodiversity, 2024)
Abstract. Rohman A, Wahyudi D, Subchan W, Jumadiawan. 2024. Bird community structure and host plant in Sukamade Resort, Meru Betiri National Park, East Java, Indonesia. Biodiversitas 25: 3295-3308. Meru Betiri National Park (MBNP), East Java, Indonesia, is classified as a conservation area. Management of Biological Natural Resources (MBNR) refers to bird communities in a habitat. Damage to biological natural resources causes a high threat of bird vulnerability and extinction. Birds play a crucial role as indicators of the environment. This research aimed to determine the community structure of birds and host plants at the Sukamade resort. We recorded 49 bird species and 21 host plants. We are actively identifying location points according to habitat variations. Resort offices have the highest diversity (H ' = 2.774). The jungle track has the highest bird evenness index (E = 0.754). Parang Kulon has the highest dominance index (D = 0.162). Pycnonotus goiavier (pg) had the highest abundance found at each location. Pavo muticus (pm) is a protected species according to Indonesian national law. A total of 21 plants were documented as the dominant vegetation. Our research revealed that Ficus benjamina (FB) had the highest frequency of visits by pollinators, and the prevailing avian behavior observed was perching. The presence of Haliaeetus leucogaster (hl) nesting on Artocarpus elasticus (AE) trees was documented. Meanwhile, the Principal Component Analysis (PCA) results showed that four bird species, namely Merops leschenaulti (ml), Rhyticeros undulatus (ru), P. goiavier (pg), Pycnonotus simplex (ps), Anthracoceros albirostris (aa)) were correlated with two host plant species (A. elasticus (AE) and Albizia chinensis (AC)). Our results demonstrate a significant link between the presence of birds and host plants, underscoring their integral role in the ecology.